PENGARUH SUBSTITUSI PUREE DAUN KELOR (MORINGA OLEIFERA) PADA TEPUNG TERIGU TERHADAP DAYA TERIMA CILOK - Sheylla Tara Audina; Badrut Tamam; I Gusti Putu Sudita Puryana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
Cilok, a typical food from Bandung, West Java, generally uses wheat flour and tapioca flour. The purpose of this study was to determine the effect of substitution of Moringa leaf puree (Moringa Oleifera) in wheat flour on the acceptability of cilok, this type of experimental research used a randomized block design (RAK) with 5 treatments, namely P1 (Moringa leaf puree substitution 2.5%), P2 ( Moringa leaf puree substitution 5%), P3 (moringa leaf puree substitution 7.5%), P4 (10% Moringa leaf puree substitution), P5 (12.5% Moringa puree substitution). Data were analyzed using ANOVA test followed by BNT test. The results of the subjective analysis of Moringa leaf cilok covering texture, color, aroma, taste, acceptability, texture quality, color quality, aroma quality, and taste quality were significant. The results of the objective analysis were the levels of iron (Fe) and antioxidant capacity. The result of the best iron (Fe) content of Moringa leaf cilok was 8.511 mg/100 g. To meet the daily needs of iron (Fe) for women, 10 cilok leaves contain iron (Fe) 17,022 mg and 5 grains of cilok moringa leaves for men contain 8,511 mg/100 g of iron. The result of the best antioxidant capacity in Moringa leaf cilok is 8.44 mg/L GAEACKeywords: Cilok, Moringa Leaf Puree, Wheat Flour